XRad17 is required for the activation of XChk1 but not XCds1 during checkpoint signaling in Xenopus. - Jones, R; Chapman, R; Puligilla, C; Murray, J; Car, A; Ford, C; Lindsay, H (2003)
The DNA damage/replication checkpoints act by sensing the presence of damaged DNA or stalled replication forks and initiate signaling pathways that arrest cell cycle progression. Here we report the cloning and characterization of Xenopus orthologues of the RFCand PCNA-related checkpoint proteins. XRad17 shares regions of homology with the five subunits of Replication factor C. XRad9, XRad1, and XHus1 (components of the 9-1-1 complex) all show homology to the DNA polymerase processivity factor PCNA. We demonstrate that these proteins associate with chromatin and are phosphorylated when replication is inhibited by aphidicolin. Phosphorylation of X9-1-1 is caffeine sensitive, but the chromatin association of XRad17 and the X9-1-1 complex after replication block is unaffected by caffeine. This suggests that the X9-1-1 complex can associate with chromatin independently of XAtm/XAtr activity. We further demonstrate that XRad17 is essential for the chromatin binding and checkpoint-dependent phosphorylation of X9-1-1 and for the activation of XChk1 when the replication checkpoint is induced by aphidicolin. XRad17 is not, however, required for the activation of XCds1 in response to dsDNA ends.